Education and Solidarity: A Path towards Educational Inclusion - Isabel Hernandez Arteaga; Karen Margarita Fernandez Lopez; Alejandra Corina Estela Vasquez; Edith Johanna Mestizo Nuzcue (Historia Social y de la Educación, 2020)
Educational inclusion is a process that is immersed in the everyday life of Colombians and that demands of each citizen a significant contribution to make this possible; for this reason, this article aims to review the existing literature on education and solidarity, which are considered complementary concepts to achieve inclusion in the country's institutions. To carry out the review, the Scielo, Dialnety and Redalyc databases were consulted, from which articles covering a time period between 2008 and 2018 were chosen. The results and conclusions show that solidarity can be taught in the school context and it is in turn would allow the formation of a human being willing to dialogue, capable to build alliances and reach agreements that benefit and facilitate coexistence among all, which would strengthen the inclusion process not from the norm, but, from a natural human action.